If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3log(2) * x + -8 = 4 Reorder the terms for easier multiplication: 3 * 2glo * x + -8 = 4 Multiply 3 * 2 6glo * x + -8 = 4 Multiply glo * x 6glox + -8 = 4 Reorder the terms: -8 + 6glox = 4 Solving -8 + 6glox = 4 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + 6glox = 4 + 8 Combine like terms: -8 + 8 = 0 0 + 6glox = 4 + 8 6glox = 4 + 8 Combine like terms: 4 + 8 = 12 6glox = 12 Divide each side by '6lox'. g = 2l-1o-1x-1 Simplifying g = 2l-1o-1x-1
| 2X-3=-7+33 | | 52=4(2j+25) | | 3+4m=15+-2m | | 17+0.08x=31.80 | | 10x/6=4 | | 3+3m=15-2m | | X-11/6=4 | | -2x(y+7)-y=7 | | 9x-2x=56 | | 70x^2+x-0.245=0 | | 34-n=20+14 | | !4.9/4 | | 2x-8+66=12x+9-6x+10 | | 15x+60=30x | | (6y)+22+(x+3)=180 | | 11x+13y=-23 | | 5.2y-13=21y+18 | | -10-4x=7x+89 | | -3+10=6x+46 | | (400-20x)(12-x)=144 | | X-10=-2+2x | | 2y-7=-7 | | y/11-3=6 | | 2x+3=-6+99 | | 9+5x=3x+23 | | 5x+1=-x+55 | | 2x+6=42-7x | | b-2+6b=30 | | F(x)=3x-6x-45 | | y=85*2.5x | | 8/9x=4/9x | | 7+7x+7x=175 |